The Effectiveness of Coffee Leather Organic Fertilizer on The Productivity of Red Spinach (Amaranthus Tricolor L.) - Ahmad Fatoni; Muhfahroyin Muhfahroyin; Agus Sujarwanta; Hening Widowati; Agus Sutanto (Politeknik Negeri Lampung., 2020)
The study to determine the effect of variations in the composition of organic fertilizer from coffee husks on the productivity of red spinach (Amaranthus tricolor L), using a completely randomized design (CRD) with one control and four treatment combinations with six repetitions carried out for 30 days. Productivity includes the height and wet weight of red spinach. Data were analyzed using Multivariate Analysis of Variance (MANOVA). In conclusion, the application of coffee husk organic fertilizer has a significant effect on the growth and productivity of red spinach, the best dose of treatment is P3 = 50% coffee husk + 12.5% ​​leaf waste + 25% livestock manure + 12.5% ​​husk charcoal.